ROMANIAN CONSUMER PREFERENCES FOR OENOTOURISM IN 2021 - Arina Oana ANTOCE; Elvis Ovidiu LOGIGAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
With 190,000 ha of vineyards and ranking 13th in the world for wine production and 14th for wine consumption, Romania has a high potential for oenotourism, which has been underexploited for years. In order to find solutions to encourage oenotourism, Romanian consumers were questioned regarding their preferences for winery visit experience such as: the distance which they would have to travel, the number of days and the amount of money they would be willing to spend and their expectations from a visit to a winery. To improve the offer and to make the information easily available to the interested wine tourists the survey included also questions regarding the approaches for obtaining information and recommendations, as well as the frequency of social media usage. The main results pointed out that Romanian wine consumers would prefer to go on trips to wineries recommended by friends rather than travel agencies, with a group of friends, for 2 or 3 days, especially in autumn, expecting to pay between 750-1,200 RON. Romanians would mostly go anywhere in Romania rather than abroad, men especially preferring to go to places reachable within 3 hours drive from their residence. The second most important information source, after the recommendation from friends, is the social media, showing the importance of advertising more on such media.